Preparing for 2020 through Action Research: The Development and Installation of an In-Service Training Programme for Japanese Elementary School Homeroom Teachers in Japan - King, David (2018)
As instructed by the Japanese Ministry of Education, Culture, Sports, Science and Technology (MEXT), from 2020, elementary school homeroom teachers in Japan will be expected to teach elementary school English lessons, a subject they are neither trained for nor experienced in. MEXT is set to implement reforms that will see an increase in English lessons for fifth and sixth graders (ages ten to twelve) from thirty-five to seventy classroom hours a year. Despite the significant lack of support, MEXT has stated that homeroom teachers for the fifth and sixth grade will be responsible for teaching the increase in English classes. This has resulted in an overwhelming sense of anxiety amongst teachers which is not being addressed by those responsible, namely MEXT, prefectural and local boards of educations, and school principles. As such, this paper set out to investigate two research questions, firstly, what impact on Japanese HRTs’ English teaching abilities can the development and implementation of a 6-week in-service action research training programme provide, and to what extent is action research an appropriate methodology to explore elementary school homeroom teacher anxiety. Conducted at the local scale, with scaffolding provided by the author, this research was carried out with five homeroom teachers, three from the fifth grade and two from the sixth grade. Action research began through initial semistructured interviews focused on the homeroom teachers’ backgrounds, opinions on current elementary school English education including their classroom role, and their opinions on the 2020 MEXT reforms. Research concluded with a semi-structured interview focused on homeroom teacher feedback and impressions a of the action research, and progress made in English teaching. This research concludes that through action research, homeroom teachers were able to take greater leadership over both classroom material preparations, including lesson plan development, as well as become more confident in teaching English. This was possible due to the suitability of action research as the chosen methodology in this research. Despite a lack of support and interest shown towards the research by those who should be taking leadership, all homeroom teachers, were able to directly address individual areas of teaching anxiety and concern, and thus were able to take the first steps towards becoming elementary school teachers of English.